LAPAROSCOPIC STAPLER APPENDECTOMY IN PEDIATRIC PATIENTS - Daniela Dobrițoiu; Alin Stoica; Simona-Gabriela Tudorache; Laura-Mihaela Ion; Iunia-Carla Floricel (Amaltea Medical Publishing House, 2021)
Introduction. Acute appendicitis is the most frequent cause of surgical abdominal pain in children. There are multiple variants of surgical treatment of acute appendicitis, including laparoscopic stapler appendectomy. Aim. We proposed to present our experience regarding laparoscopic stapler appendectomy as an alternative treatment method in children diagnosed with appendicitis. Material and method. In this retrospective descriptive, observational study we analyzed the data of children admitted with appendicitis to Ponderas Academic Hospital between January 2018 and October 2020. Results. 78 laparoscopic appendectomies were performed in children with ages of 3 to 16 years old. Of these, 70 were performed using mechanical suturing devices. Time of surgery was 77 minutes in 2018, 76 minutes in 2019 and 91 minutes in 2020. In 2020 the number of complicated appendicitis was double than in 2019 and six times higher than in 2018 but time of surgery was smaller in these cases in 2020 with longer hospital stay. Conclusions. In 2020 we observed that was a smaller number of patients operated, with higher time of surgery, length of hospital stay, more complicated appendicitis (regarding drainage usage) but with smaller time of surgery in these complicated cases which indicates the effectiveness of using the stapler.